TINGKAT KEPUASAN PESERTA PELATIHAN KERJA ATAS KUALITAS PELAYANAN DINAS PENANAMAN MODAL, PELAYANAN TERPADU SATU PINTU DAN TENAGA KERJA KOTA PROBOLINGGO (Study Kasus Pada Unit Pelaksana Teknis Daerah Balai Latihan Kerja) - Imam Sucahyo; Renny Puspitarini; Renanda Maulina (Journal of Innovation Research and Knowledge, 2022)
This research was conducted at the UPTD Job Training Center Probolinggo City with the research objectives to be achieved are (1) To find out the results of the level of satisfaction of the training participants on the service quality of the UPTD Job Training Center Probolinggo City employees (2) To determine the service quality of the UPTD Job Training Center employees City of Probolinggo given to training participants (3) To be able to explain quantitatively descriptive which is useful for measuring the level of satisfaction of training participants on the quality of employee services. This population is all job training participants totaling 160 participants at the UPTD Job Training Center Probolinggo City, with a sampling technique, namely non-probability sampling, namely purposive sampling (criteria sample) so that it becomes a sample with a total of 114 particapants. The type of research used in this research is quantitative research with the variables used include requirements, system mechanism procedures, completion time, costs/tariffs, product specifications, types of services, competencies, implementing behavior, handling complaints suggestions and inputs, facilities and infrastructure. The results showed that the indicator that had the highest IKM value was 3.37 with a conversion value of 84.3 with a weighted value of "B" in the "Good" category, while the lowest value was 3.07 with a conversion of 76.8 with a weight of "B" still included in the "B" category. Well". The value of the community satisfaction index, the IKM value of the 9 IKM elements, is 0.11111 and the IKM conversion value is 79.33. This means that the service quality of the Probolinggo City Work Training Center UPTD is declared to be good.